Cultivating Reflective Islam: Ngaji Filsafat and Eclectic Religious Expressions among Urban Muslim Youth in Digitalizing Indonesia - Anoraga, Bhirawa; Kailani, Najib; Misbah, Aflahah (Digital Muslim Review, 2025)
This study investigates the growing popularity of Ngaji Filsafat, a phenomenon cultivating a reflective Islam that offers an alternative study group for young Muslims in Yogyakarta and beyond. This mosque-based gathering eschews conventional texts like the Qur’an, instead exploring ideas from thinkers both Muslim and non-Muslim, from Greek philosophers to contemporary intellectuals. Its rise presents an anomaly within the conservative-turn thesis, given its broad appeal and promotion of pluralist teachings. Drawing on observations and in-depth interviews with initiators and attendees, the study finds its appeal lies not in aspirations for heightened piety or religious activism. Rather, for urban Muslim youth, it functions as a space offering interpretive resources for navigating everyday challenges within a neoliberal context. These findings highlight the need for alternative frameworks, beyond piety-centered or conservative-pluralist paradigms, to understand diverse Islamic expressions in digitalizing post–New Order Indonesia. Furthermore, against scholarship emphasizing the state’s coercive role in civic pluralism, this study illuminates how non-state actors mainstream pluralist Islamic engagements.